Verona integron encoded metallo Beta lactamase (VIM) and Vietnam extended spectrum Beta lactamase (VEB) producing Pseudomonas balearica from a clinical specimen - Uddin, Fakhur; Muhammad Sohail; Qurban Hussain Shaikh; Mir Tahir Hussain; Kerry Roulston; Timothy Daniel McHugh (Journal of the Pakistan Medical Association, 2022)
Pseudomonas balearica, a saprophyte found in marshy and marine habitats, is not routinely differentiated from P. aeruginosa and P. stutzeri using automated systems and hence has not been reported from clinical samples. This study describes the identification of P. balearica using MALDI-TOF-MS and 16S rDNA sequence from a patient admitted to an intensive care unit (I.C.U.). The isolate was found to be Verona integron-mediated Metallo-Beta-lactamase (V.I.M.), and Vietnam extended-spectrum Beta-lactamase (V.E.B.) producer and resistant to Ceftriaxone, Imipenem, and Tobramycin. P. balearica can be a source for horizontal transfer of blaVEB and blaVIM. Its pathogenesis has yet to be understood. Continue...